Characterization of Resistance Patterns and Detection of Apramycin Resistance Genes in Escherichia coli Isolated from Chicken Feces and Houseflies after Apramycin Administration - Zhang, Anyun; Li, Yunxia; Guan, Zhongbin; Tuo, Hongmei; Liu, Dan; Yang, Yanxian; Xu, Changwen; Lei, Changwei; Wang, Hongning (Frontiers in Microbiology, 2018)
The aim of this study was to evaluate the influence of apramycin administration on the development of antibiotic resistance in Escherichia coli (E. coli) strains isolated from chicken feces and houseflies under field conditions. Chickens in the medicated group (n=25000) were given successive prophylactic doses (0.5 mg/L) of apramycin in their drinking water from Days 1 through 5, while no antibiotics were added to the un-medicated groups drinking water (n=25000). Over 40 days, a total of 1170 E. coli strains were isolated from fecal samples obtained from medicated and un-medicated chickens and houseflies from the same chicken farm. Apramycin MIC90 values for E. coli strains obtained from the medicated group increased 32-128 times from Days 2 to 6 (256μg/ml to 1024 μg/ml) when compared to those on Day 0 (8 μg/ml). Strains isolated from un-medicated chickens and houseflies had consistently low MIC90 values (8 μg/ml to 16 μg/ml) during the first week, but showed a dramatic increase from Days 8 to 10 (128μg/ml to 1024 μg/ml). The apramycin resistance gene aac(3)-Ⅳ was detected in E. coli strains from medicated (n=71), un-medicated (n=32), and housefly groups (n=42). All strains positive for aac(3)-Ⅳ were classified into 12 pulsed-field gel electrophoresis (PFGE) types. PFGE type A, E, and G were the predominant types in both the medicated and housefly groups, suggesting houseflies play an important role in spreading E. coli resistant strains. Taken together, our study revealed that apramycin administration could facilitate the occurrence of apramycin-resistant E.coli and the apramycin-resistance gene acc(3)-IV. In turn, these strains could be transmitted by houseflies, thus increasing the potential risk of spreading multi-drug resistant E. coli to the public.